Universidad fluvial del sur de Colombia Río Caquetá y Orteguaza (2022)
he present project of degree work consists of the design of a navigable educational equipment type itinerant ship equipped with technological and pedagogical infrastructure that allows providing higher education in the points of greatest concentration of population for the docking of the ship, which will work according to the demand for educational programs of the population in the areas of the eleven riverside municipalities of the Caquetá and Orteguaza rivers in southern Colombia, considering the geographic, social and economic isolation of this area of The development o the country. f this novel proposal is based on giving a level of professional schooling to the population of marginal areas to help improve one of the most common problems that are evident in remote rural areas of the country, such as academic inequality between the se ctor rural and urban. In addition, it will strengthen the socioeconomic and cultural conditions of the beneficiary families, preventing the displacement of these communities to other areas of the country and, in the same way, reducing the entry of young pe ople into armed groups and reducing the planting of illicit crops through the modernization of the countryside and promoting the economic development of the region in the medium and long term. Keywords: itinerant boat, docks, docking, higher education, r displacement, armed group, professional. iverside areas, rural area.